Managerial Decisions in MSMEs: A Praxiological Approach to Indonesian Entrepreneurs - Gustiawan, Wahyu Dede; Kristianingsih, Yuyun (Fakultas Ekonomi Universitas Kadiri, 2025)
Managerial decision-making in Micro, Small, and Medium Enterprises (MSMEs) has a very important role in determining business sustainability and growth, especially in Indonesia. This article aims to analyze a praxiological approach in the decision-making process among Indonesian MSME entrepreneurs using the Systematic Literature Review (SLR) method. This research identifies and synthesizes related literature from various relevant academic sources in a certain period of time. The results of the study show that the praxiological approach, which emphasizes the relationship between theory and practice, helps entrepreneurs in dealing with the complexities of the business environment and improving the effectiveness of strategic decisions. The findings of this study also reveal that contextual factors such as business culture, access to resources, limited data and knowledge, and access to technology affect the decision-making process. This article makes a theoretical contribution to the development of managerial decision-making studies and offers practical recommendations for MSME entrepreneurs and policymakers in Indonesia.